2020
DOI: 10.1111/clr.13664
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors influencing implant positioning by guided surgery using a nonmetal sleeve template in the partially edentulous ridge: Multiple regression analysis of a prospective cohort

Abstract: Objective: To determine the positional accuracy of implants placed with a threedimensionally printed template having nonmetal sleeves and to determine the contributing factors to observed deviations. Materials and Methods: One hundred and eighty-seven implants placed in 72 patients were analyzed. Presurgical intraoral scans and cone-beam computed tomography images obtained before and after surgery were superimposed, and vertical, angular, platform, and apex deviations were measured between the virtually planne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 38 publications
(64 reference statements)
3
37
0
Order By: Relevance
“…The accuracy of both VG and NG in the present study seemed reliable when compared to the outcomes from the previous experiments [ 13 , 14 , 15 , 16 ] which reported that stereolithographic surgical guides caused angular and linear deviations ranging between 3° and 4° and 1 mm and 2 mm on average, respectively. Furthermore, a recent systematic review and a meta-analysis of 20 randomized clinical trials revealed that the total mean linear deviation of 1.2 mm (platform level) and 1.4 mm (apex level) and the total mean angular deviation of 3.5° [ 17 ] were similar to the ones observed in this study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The accuracy of both VG and NG in the present study seemed reliable when compared to the outcomes from the previous experiments [ 13 , 14 , 15 , 16 ] which reported that stereolithographic surgical guides caused angular and linear deviations ranging between 3° and 4° and 1 mm and 2 mm on average, respectively. Furthermore, a recent systematic review and a meta-analysis of 20 randomized clinical trials revealed that the total mean linear deviation of 1.2 mm (platform level) and 1.4 mm (apex level) and the total mean angular deviation of 3.5° [ 17 ] were similar to the ones observed in this study.…”
Section: Discussionsupporting
confidence: 84%
“…The preoperative and postoperative datasets with a merged layer of the abutment design were superimposed to each other using adjacent teeth as references. In the VG group, the angle and the centers of the platform and the apex of the virtually planned implant were determined based on the depth and axis of the drilling hole which had been formed in the VG, while those of the actually placed implant were deduced using the reverse engineering technique as explained in the previous study [ 14 ], visualizing inversely from the design of the abutment. In the NG group, both presurgical and postsurgical locations of the angle and the centers of the platform and the apex of the fixture were determined using the reverse engineering technique.…”
Section: Methodsmentioning
confidence: 99%
“…It could be then no significant difference for the patient if extensive surgery is done guided or freehand and the same difference may be significant for less extensive surgery. Also accuracy of guided implant placement vary if that is a simple or complex surgery [6,19]. The same time required for accurate guide stabilization with bone anchors during extensive surgery may disappear when comparing time required to make similar surgery freehand without this process.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of in vitro and in vitro studies, as well as systematic reviews, clearly lead to the conclusion that using individual CAD/CAM (Computer-aided design/Computer-aided manufacturing) guides may be the best way to achieve great accuracy and remain in line with the concept of prosthetically driven treatment plan in implant dentistry [1][2][3][4][5][6]. Stereolithographic surgical guides are also one of the most popular application of 3D printing in oral and maxillofacial surgery [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation